2019
DOI: 10.3390/app9193942
|View full text |Cite
|
Sign up to set email alerts
|

Does Apical Papilla Survive and Develop in Apical Periodontitis Presence after Regenerative Endodontic Procedures?

Abstract: Regenerative endodontic procedures (REPs) have emerged as a treatment option for immature necrotic teeth to allow the reestablishment of a newly formed vital tissue and enable continued root development. The apical papilla stem cells (SCAPs) play an important role in physiologic root development and may also contribute to further root development during REPs. The goal of these case reports is to show evidence of the apical papilla survival and development, in human teeth with apical periodontitis, after REPs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 33 publications
3
44
0
Order By: Relevance
“…These autogenous cells along with the blood clot will facilitate both pulp regeneration and continuing root tissue formation [16][17][18]. Also, another study revealed the survival and differentiation of the apical papilla and Hertwig's epithelial root sheath after endodontic infection, with clinical radiographic and histological evidence after REP [19].…”
Section: Discussionmentioning
confidence: 99%
“…These autogenous cells along with the blood clot will facilitate both pulp regeneration and continuing root tissue formation [16][17][18]. Also, another study revealed the survival and differentiation of the apical papilla and Hertwig's epithelial root sheath after endodontic infection, with clinical radiographic and histological evidence after REP [19].…”
Section: Discussionmentioning
confidence: 99%
“…The positive result of the regenerative protocol depends on various circumstances, which are considered below. An infected immature permanent tooth with an open apex exhibits greater potential to achieve a positive result of endodontic treatment than mature teeth, due to rich vascularization, a significant supply of dental pulp stem cells (DPSC) [61], the reservoir of stem cells from apical papillae (SCAP), and their ability to produce the primary odontoblasts involved in apexogenesis [12,20,21,92]. However, one of the major problems of necrotic immature teeth is controlling the infection by obtaining a complete eradication of bacterial biofilm in the complex root canal system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although the present study focuses on a technical improvement of the root-end preparation, it is important to bear in mind that the success of endodontic microsurgery requires the creation of a favorable apical microenvironment that allows further healing of periapical tissues, which implies the recruitment of growth factors and cellular differentiation [ 67 , 68 , 69 ]. Thus, after preparing the apical cavity, root-end filling should include the use of a biocompatible and bioactive material, such as MTA or Biodentine, which promotes the repair/regeneration of the apical tissues [ 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%